Rural Special Education Teachers as Consultants: Roles and Responsibilities - Linda P. Thurston; Ilene Kimsey (Educational Considerations, 1989)
The unique characteristics of rural schools and teachers create advantages as well as barriers to the indirect service delivery model of consulting.